Hemolytic uremic syndrome (HUS) - case report - Aleksandra Borkowska; Anna Sobstyl; Aleksandra Chałupnik; Zuzanna Chilimoniuk; Maciej Dobosz; Szymon Marosz (Kazimierz Wielki University, 2020)
Introduction Hemolytic uremic syndrome (HUS) is characterized by hemolytic anemia, thrombocytopenia and acute renal failure. In 90% of children, HUS most often develops after an intestinal infection caused by verotoxin-producing E. coli. The remaining 10%, without any preceding diarrhea, are diagnosed with atypical HUS. Aim The objective of the study was the presentation the case of two patient with hemolytic uremic syndrome. Results The case report concerns two patients diagnosed with haemolytic uremic syndrome. Both cases shared many symptoms. Initially gastroenteritis, dehydration followed by thrombocytopenia, renal failure and anemia. These are examples of a typical hemolytic uremic syndrome. Many additional tests were carried out, including morphology, urinalysis, blood chemistry, but the final diagnosis was made on the basis of the clinical picture and the triad of symptoms typical of HUS. Conclusions Hemolytic uremic syndrome is a disease that threatens the life of a child. It is important to recognize symptoms as soon as possible and begin treatment to prevent dangerous complications.